Avaliando a aprendizagem de língua inglesa em uma escola de ensino médio a partir de contribuições discentes - Paiva, Vitória Maria Avelino da Silva (2012)
This study discusses the evaluation of the English language‟s learning developed in a public high school from Lajes-RN in 2011 starting from a qualitative evaluation proposal (SAUL 1988; CANAN, 1996; DEMO, 2008) aiming the production of knowledge about the evaluation process developed in the classes of English language involving the contributions from students. To diagnose and characterize the evaluation process of English language of the researched school, identifying the representations that students attributed to the evaluation, we have implemented the evaluation instruments suggested by students to perform the evaluation of language learning and allowed a reflection about the student‟s participation in the construction of the evaluation process of the English language, subject discussed by Sant‟anna (2002) and other theorists (CANAN, 1996; BRAZIL, 2002; PEREIRA, 2009). To conduct the research work, we use the qualitative approach with ethnographic basis, substantiate in authors like Bogdan, Biklen (1994), Mazzotti; Gewandsznajder (1998), Strauss, Corbin (2008) among others. The methodology was the action research (ANDRÉ, 1995; NUNAN, 2007; LANKSHEAR; KNOBEL, 2008) described as research of empirical basis which associates an action with a resolution of a collective problem, because in it, its researchers and employees are engaged in a cooperatively way (THIOLLENT, 1985). When we treat about the evaluation of English language‟s learning (ALMEIDA FILHO, 1993; SCARAMUCCI, 2009) practiced before and after the contributions made by the students of the second year of the refereed school, the study considers that high school students have a more critical and reflective conscience with regard to their evaluations, not just opining on the assessment of learning English but also about the assessment of other subjects from their scholar curriculum and so this research presents possibilities for performing the act of evaluation which consider the participation of students in decisions regarding this process, because we cogitate that when the teachers share the decisions with their students, teachers can add quality to the evaluation process